(3KGhPhSjhS aj GdGcQs - (3KGOPhSjhSs; (3KGhPhSjhSs
(3ChdgG (B:s
(3GdcQg gi Tcd eLSe jMjWg SWM hGMO LejY GdNWhW GdeSJbjeI GdJi JNQL ef GdfbWI hGMOg s
(3BNQgG (B:s
(3CYXe cKjQkG ef ajg bWGY hPdc eG CQOfG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B142s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs